Factors Influencing for Choosing Online Novel Platform Service of Interested Writers in Mueang District, Samut Prakan Province - Sribantao, Jantima; Vijchulata, Chanin; Sukchoknithiphokin, Thanatnan; Sangrod, Putthachat (Rajapark Journal, 2023)
This research aimed to (1) study factor for choosing the online novel platform service (2) compare way of choosing the online novel platform service according to personal factor, and (3) study the factors influencing way of choosing the online novel platform service, a sample of people interested in being a writer in Mueang District Samut Prakan Province, a total of 385 people used a questionnaire as a tool to collect data. The statistics used in the data analysis represent mean, standard deviation, t-test, one-way ANOVA and multiple regression analysis. The results of the research revealed that; 1) factors for novel writing skills of novel writing and the acceptance of innovation and technology were at the highest 2) The writers with different age, education level, occupation and average monthly income were different way of choosing the online novel platform service, and 3) factors regarding knowledge of the novel writing aspect and acceptance of innovation and technology aspect influenced their motivation for choosing the online novel platform service. These two variables could explain the change in the variable for choosing the online novel platform service got 50.04%.